Factors influencing entrepreneurial intention among undergraduates in Universiti Kebangsaan Malaysia (UKM) / Noor Syairah Nordin and Siti Nur Syahirah Rosdi - Nordin, Noor Syairah; Rosdi, Siti Nur Syahirah (Faculty of Business and Management, 2015)
This research was conducted to carry out a study entitled “Factors Influencing Entrepreneurial Intention among Undergraduates in Universiti Kebangsaan Malaysia (UKM)”. The purpose of this study is to investigate the key factors which lead to the entrepreneurial intention among undergraduates. The three independent variables are entrepreneurial educational support, family influence, and self-efficacy. The sample size used for this study was 150. Data was obtained by using convenience sampling. The study seeks to identify the level of entrepreneurial intention among undergraduates in Universiti Kebangsaan Malaysia (UKM), to examine the relationship between independent variables (entrepreneurial educational support, self-efficacy, and family influence) and dependent variable (entrepreneurial intention) and to identify the most significant predictor variable on entrepreneurial intention among undergraduates in Universiti Kebangsaan Malaysia (UKM). Finding shows that, there is an entrepreneurial intention among undergraduates in Universiti Kebangsaan Malaysia (UKM) and all independent variables (entrepreneurial educational support, self-efficacy, and family influence) show significant relationship with the dependent variable (entrepreneurial intention). The most significant predictor variable on entrepreneurial intention among undergraduates in Universiti Kebangsaan Malaysia (UKM) is family influence at 0.366 (36.6%). Overall, researchers achieved to answer all objectives in the study.